“Shrinking Cities”, the concept of urban shrinkage in different realities: a systematic review - Lêdo, Maria Gabriela Silva; Fontes, Maria Solange Gurgel de Castro; Anjos, Maximiliano dos; Magagnin, Renata Cardoso (Revista Nacional de Gerenciamento de Cidades, 2023)
The scientific literature on the term “shrinking cities” is recent, but translates an ancient phenomenon previously expressed, almost exclusively, by the term urban decline. In the mid-2000s, the new term gained prominence and began to have added meaning. Today, there is an effort to understand urban shrinkage as a global, multidisciplinary and multiscale phenomenon with multicriteria analysis. To identify how different authors work with this new approach, a systematic review of academic papers published in the SCOPUS and Web of Science databases was used. The results are scored from the general characterization of the research, the multiplicity of subjects that involve the term, the different analysis criteria for the same phenomenon, the need for a multidisciplinary analysis, the inequality in the places of study and the changes in the meaning of the expression according to the condition. The main discussions of the 19 works, which were part of the sample size, are conducted in relation to the origin/meaning/parameter of analysis of the term or, even, about its applicability in different places through case studies. Thus, the present study seeks to discuss how the term urban shrinkage transposes different contexts.